2016
DOI: 10.11646/zootaxa.4194.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters

Abstract: We have compiled available records in the literature for medusozoan cnidarians and ctenophores of South America. New records of species are also included. Each entry (i.e., identified species or still as yet not determined species referred to as "sp." in the literature) includes a synonymy list for South America, taxonomical remarks, notes on habit, and information on geographical occurrence. We have listed 800 unique determined species, in 958 morphotype entries: 5 cubozoans, 905 hydrozoans, 25 scyphozoans, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,464 publications
(92 citation statements)
references
References 0 publications
3
81
0
8
Order By: Relevance
“…3). Recently, Oliveira et al (2016) considered this medusa as integrating the Brazilian fauna based on Kramp's (1957) record at 31.27°S, 29.94°W (number 4 in Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3). Recently, Oliveira et al (2016) considered this medusa as integrating the Brazilian fauna based on Kramp's (1957) record at 31.27°S, 29.94°W (number 4 in Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…4). Although there were some previous records of this species on Brazilian waters (Ranson, 1949;Kramp, 1959b), these occurrences were overlooked in a recent review (Oliveira et al, 2016), perhaps because they were reported only as "Atlantic" or "Equatorial Atlantic". Thus, this study highlights the presence of P. triloba in oceanic waters offshore northern Brazilian coast.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stephanoscyphistoma simplex (Kirkpatrick, 1890) (Goy, 1979;Silveira & Morandini, 1997;Morandini, 2003;Oliveira et al, 2016). In addition, four more polyp forms occur in the Brazilian coast, but only identified to the generic level as Nausithoe sp.…”
Section: Introductionmentioning
confidence: 99%